Review Impact of Compressed Breast Thickness and Exposure Parameters on Mean Glandular Dose (MGD) in Full-Field Digital Mammography Examination - Victory, Vivi Sumanti; Noor, Johan Andoyo Effendi; Widodo, Chomsin Sulistya; Arifin, Zaenal (Journal of Physics and Its Applications, 2025)
The purpose of this paper is to review and summarize the relationship between the average mammary gland dose (MGD) and compressed breast thickness (CBT) in digital mammography. The relationship between MGD and CBT, measured using a dosimeter, shows that the thicker the breast, the higher the MGD. However, the relationship between MGD and CBT using patient data (i.e., actual MGD values) may not be directly proportional to CBT because it can be influenced by other factors, such as age. MGD values are directly proportional to CBT when based on phantom measurements. Across various brands and types of mammography units, MGD values are not always directly proportional due to differences in K patterns (incident air kerma), which create different automatic exposure control (AEC) modes. In conclusion, CBT has a complex relationship with MGD. In general, MGD is positively correlated with CBT because increasing breast thickness requires a higher radiation dose to produce optimal image quality. However, this relationship is not always linear and can be negatively correlated under certain conditions, considering the influence of other parameters that can affect both CBT and MGD.